Voltammetric Determination of Flunixin on Molecularly Imprinted Polypyrrole Modified Glassy Carbon Electrode - Radi, Abd-Elgawad (J Anal Methods Chem, 2016)
A novel electrochemical sensing approach, based on electropolymerization of a molecularly imprinted polypyrrole (MIPpy) film onto a glassy carbon electrode (GCE) surface, was developed for the detection of flunixin (FXN). The sensing conditions and the performance of the constructed sensor were assessed by cyclic, differential pulse and (DPV) square wave voltammetry (SWV). The sensor exhibited high sensitivity, with linear responses in the range of 5.0 to 50.0 µM with detection limits of 1.5 and 1.0 µM for DPV and SWV, respectively. In addition, the sensor showed high selectivity towards FXN in comparison to other interferents. The sensor was successfully utilized for the direct determination of FXN in buffalo raw milk samples.